A Damsel in Distress - Wodehouse, P. G. (Pelham Grenville), 1881-1975 (Salt Lake City, UT : Project Gutenberg, 2000)
"A Damsel in Distress" by P. G. Wodehouse is a novel published in 1919. When American composer George Bevan encounters a mysterious young woman fleeing into his taxicab in London, he falls instantly in love. Tracking her to a grand country estate, George discovers she's Lady Maud Marsh$1 (Bbut she's in love with someone else entirely. Amid mistaken identities, scheming relatives, and a servants' sweepstake on Maud's marriage prospects, romantic chaos ensues at Belpher Castle in this comedic tale of love and misunderstanding. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Damsel_in_Distress_(novel)
Release date is 2000-06-01
Produced by Jim Tinsley
Keywords: Humorous stories; Nobility -- Fiction; Blandings Castle (England : Imaginary place) -- Fiction; Shropshire (England) -- Fiction